Flammeascoma ryskae sp. nov. (Pleosporales, Anteagloniaceae) as a new pigment—producing species of European floodplain forest habitats - Mlčoch, Patrik; Matušinský, Pavel (Phytotaxa, 2025)
The relatively recently described family Anteagloniaceae has four genera—Anteaglonium, Flammeascoma, Purpureofaciens and a newly defined monotypic genus Neolophiotrema. The newly described species Flammeascoma ryskae sp. nov. is the first species of this genus found in Europe so far. It was found during an ecological study of fungal diversity in floodplain forests at selected locations in the Czech Republic. As one of the four species of this family so far known, this new species is characterized by the production of a reddish pigment in the agar medium. In this study, in addition to the description of the new species, the current knowledge about the family Anteagloniaceae is summarized, including a discussion of their secondary metabolism.